2008
DOI: 10.1007/s10544-007-9142-7
|View full text |Cite
|
Sign up to set email alerts
|

On-chip acidification rate measurements from single cardiac cells confined in sub-nanoliter volumes

Abstract: The metabolic activity of cells can be monitored by measuring the pH in the extracellular environment. Microfabrication and microfluidic technologies allow the sensor size and the extracellular volumes to be comparable to single cells. A glass substrate with thin film pH sensitive IrO x electrodes was sealed to a replica-molded polydimethylsiloxane (PDMS) microfluidic network with integrated valves. The device, termed NanoPhysiometer, allows the trapping of single cardiac myocytes and the measurement of the pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In earlier work, Castellarnau et al used dielectrophoresis to localize high concentration suspensions of bacteria near an ISFET pH sensor and measured the acidification of the cells in the presence of glucose.29 While this technique was well suited to measurement of the bulk response, it lacks the ability to resolve the unique activity of single cells. The single cardiac cell pH system of Ges et al 15 provides the ability to monitor large adherent cells, but the volume displacement caused by sealing the channel makes it difficult to direct the cell attachment. DNA-barcode capture provides the advantage of directed capture of both adherent and naturally non-adherent cells, such as T and B cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier work, Castellarnau et al used dielectrophoresis to localize high concentration suspensions of bacteria near an ISFET pH sensor and measured the acidification of the cells in the presence of glucose.29 While this technique was well suited to measurement of the bulk response, it lacks the ability to resolve the unique activity of single cells. The single cardiac cell pH system of Ges et al 15 provides the ability to monitor large adherent cells, but the volume displacement caused by sealing the channel makes it difficult to direct the cell attachment. DNA-barcode capture provides the advantage of directed capture of both adherent and naturally non-adherent cells, such as T and B cells.…”
Section: Resultsmentioning
confidence: 99%
“…Ges et al recently demonstrated a device for on-chip measurement of acidification rates from single cardiac myocytes using physical confinement. 15 In their system, single myocytes were isolated in the sensing volume by physically pinching closed the ends of a PDMS channel. While this system represents an important step in single cell monitoring, the cell isolation technique does not allow for controlled capture on the sensor electrodes, which would be necessary for spatially resolved multi-analyte monitoring from single cells.…”
Section: Introductionmentioning
confidence: 99%
“…Heart models in microsystems presented in literature allow research on the single cells level (Kaneko et al, 2007, Ges et al, 2008, Murthy et al, 2006, Cheng et al, 2006, multicellular cultures (Nguyen et al, 2009, Nguyen et al, 2015, Pong et al, 2011, Annabi et al, 2013, Ren et al, 2013, Grosberg et al, 2011 and 3D tissue tests (Huang et al, 2007b, Horiguchi et al, 2009, Cheah et al, 2010, Chen et al, 2013 (Table 1). These microsystems are more representative experimental models of the in vivo environment, than conventional culture dishes.…”
Section: Heart Tissue Culture and Toxicity Analysismentioning
confidence: 99%
“…Extending our existing μL-scale electrochemical technologies [15,16,17,18], we are now combining at the nL scale optical and electrochemical technologies to record dynamic changes in acidification rate, oxygen and glucose consumption, lactate release, intracellular calcium concentrations, transmembrane potentials, and NADH concentrations. Sensitivities approaching that required to monitor single cells have been achieved in preliminary work [19,20,21,22,23,24]. Together these technologies are ideal for studying paracrine and autocrine signaling dynamics.…”
Section: Introductionmentioning
confidence: 99%